First day on earth - Castellucci, Cecil 1969- (Scholastic Press, 2011)
A startling novel about the true meaning of being an alien in an equally alien world
Keywords: Aliens / Juvenile fiction; Teenagers / Juvenile fiction; Science fiction; Aliens / Fiction; Teenagers / Fiction